Research on the Planning Strategy for Jianyang Aviation City on Rail Transit - LIU Wujun; TANG Wei; LI Qianlin (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] The commissioning and rapid development of Chengdu Tianfu International Airport have brought significant opportunities and challenges to the urban development of Jianyang City. It is an urgent issue to make effective planning for Jianyang Aviation City. [Method] According to the development law of airport-related industry and utilizing the advantages of rail transit to greatly promote industries, the planning strategy of Jianyang Aviation City is discussed from several aspects, including urban spatial planning, integrated transportation and hub systems, and rail transit network planning. [Result & Conclusion] The development of Jianyang airport-related area is expected to create two airport industrial chains: the business passenger flow life chain and the freight logistics industry chain. The planning and construction of rail transit ring in Jianyang City will greatly promote the integration of airport, airport-related industries and the city, playing a crucial role in the development of Jianyang Aviation City.